2018
DOI: 10.1080/02671522.2018.1452962
|View full text |Cite
|
Sign up to set email alerts
|

Learners’ attitudes to mixed-attainment grouping: examining the views of students of high, middle and low attainment

Abstract: There is a substantial international literature around the impact of different types of grouping by attainment on the academic and personal outcomes of students. This literature however is sparse in student voices, especially in relation to mixed-attainment practices. Research has indicated that students of different attainment levels might have different experiences and views of grouping structures. This paper represents a significant contribution to this literature.Drawing on the data collected as part of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
1
28
0
4
Order By: Relevance
“…A potentially significant difference was that School S was co-educational whilst School M was an all-girls school and this is a limitation of the study. A pragmatic issue was that there were relatively few secondary schools which operate mixed attainment grouping in mathematics across a number of years (Tereshchenko, et al 2018) whilst having similarities in other aspects. As Gorard (2013) notes, it is never possible to match comparator groups on all factors and we return to this particular difference between the schools later within our conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…A potentially significant difference was that School S was co-educational whilst School M was an all-girls school and this is a limitation of the study. A pragmatic issue was that there were relatively few secondary schools which operate mixed attainment grouping in mathematics across a number of years (Tereshchenko, et al 2018) whilst having similarities in other aspects. As Gorard (2013) notes, it is never possible to match comparator groups on all factors and we return to this particular difference between the schools later within our conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Teachers, with support from school leaders, can reduce the impact of bias in academic assessment by using clearly defined and objective evaluation criteria (Quinn, 2020). They can also reduce the impact of bias in academic tracking by using objective criteria for and increasing the frequency of tracking allocations (Francis, Taylor, & Tereshchenko, 2019b; Francis, Hodgen, Tereshchenko, & Archer, 2018; B. Taylor et al., 2019), by improving the richness of the curriculum and quality of the teaching in low‐attainment tracks (Dunne, Humphreys, Dyson, Sebba, Gallannaugh, & Muijs, 2011; Francis et al., 2018), or by replacing tracking with mixed‐ability groupings or groupings by specific activity (Boaler, 2008; Francis et al., 2019b; Mijs, 2016; Tereshchenko et al., 2019). Teachers can also reduce the impact that unconscious bias might have on the trust that students place in them.…”
Section: The Identities In Context Model: Linking Contextual Variatiomentioning
confidence: 99%
“…Researchers suggest that the greatest collective benefit to students is when discussion occurs in mixed-ability small groups (Cohen, 1994;Lou et al, 1996). In particular, students with low prior achievement recognise the benefits of participating in mixed ability groups (Tereshchenko et al, 2018) and have been shown to benefit in recall and problem solving (Hooper & Hannafin, 1988) and higher order thinking (Tudge, 1990). Higher order thinking occurs in small group interactions when the problems chosen are illstructured, involving conceptual learning and production of hypotheses and argumentation to find elaborated answers (Cohen, 1994;King, 2002).…”
Section: Effect Of Social Environment On Conceptual Changementioning
confidence: 99%